A Beginner’s Guide to Water Management—Aquatic Plants in Florida Lakes - Florida LAKEWATCH; Mark Hoyer (EDIS, 2014)
This circular represents a summary of current knowledge on aquatic plants and aquatic plant management strategies, highlighting the Florida situation. The major focus of this circular is the management of aquatic plants as opposed to dealing with nutrients, algae, or water clarity. Included are sections on aquatic plant biology, aquatic plant management problems, and aquatic plant management techniques. This 43-page guide was written by Florida LAKEWATCH; reviewed by Mark Hoyer, and published by the UF Department of Fisheries and Aquatic Sciences, June 2014.